RESULTS OF TESTING OAT BREEDING MATERIAL IN THE TAIGA ZONE OF WESTERN SIBERIA - G. N. Komarova; A. V. Sorokina (Труды по прикладной ботанике, генетике и селекции)
The studies found out that the productivity and quality of oat crop accessions were influenced by the climatic conditions during the vegetation period and plant mineral nutrition level. Under favorable weather and soil conditions the accessions demonstrated a reliable yield increase (0.35-0.37-0.40 t/ha), increased weight of 1000 grains and lesser grain husk. With irregular heat and humidity on poor naturally fertile soils, the growing season of mid-ripening varieties was longer, while for mid-early ones becamer shorter; grain yield was lower than in dry environments.